Evidence and suggested therapeutic approach in psoriasis of difficult-to-treat areas: Palmoplantar psoriasis, nail psoriasis, scalp psoriasis, and intertriginous psoriasis - Nilendu Sarma (Wolters Kluwer Medknow Publications, 2017)
Psoriasis is resistant to treatment and it shows frequent relapse; systemic treatment is often associated with toxicities, and long-term safety data are lacking for most of the newer drugs like biologics. Moreover, some body areas such as hands, feet, intertriginous areas, scalp, and nails are even more resistant. Frequently, systemic treatments are necessary considering the higher psychological impact on the patient. There is a lack of agreement on the best therapeutic modalities in the management of psoriasis involving difficult-to-treat locations. At present, there are no Indian guidelines for these conditions. Available literature has been reviewed extensively on the treatment of psoriasis involving difficult-to-treat locations; level of evidence has been evaluated as per the Oxford Centre for Evidence-Based Medicine 2011 guideline, and therapeutic suggestions have been developed. Best care has been employed to consider socioeconomic, cultural, genetic, and ethnic factors to prepare a therapeutic suggestion that is appropriate and logical to be used among Indian population and people of similar ethnic and socioeconomic background.